Carrying out Socio-Labour Relations on the Principles of Social Partnership Осуществление социально-трудовых отношений на принципах социального партнерства - Iastremska Olena M.; Popova Anna A. (Bìznes Inform, 2013)
The goal of the article is to study social partnership as a necessary condition of overcoming contradictions in the sphere of socio-labour relations, to reveal content of the “social partnership” notion, to reveal factors and conditions that influence effectiveness of its performance between employees, employers and state, and to identify indicators, which should be used for assessment of the level of manifestation of social partnership. The study helped to mark out main quantitative and qualitative indicators that would allow conducting monitoring of the existing state of social partnership under conditions of an individual company and state control over making managerial decisions under conditions of a rather dynamic system of socio-labour relations. Further studies in this direction should be oriented at development of theoretical foundations and development of efficient mechanisms of regulation of socio-labour relations. Цель статьи заключается в исследовании социального партнерства как необходимого условия преодоления противоречий в сфере социально-трудовых отношений, раскрытии содержания понятия «социальное партнерство», выявлении факторов и условий, влияющих на эффективность его осуществления между работниками, работодателями и государством, а также определении показателей, по которым целесообразно оценивать уровень проявления социального партнерства. В результате исследования были выделены основные количественные и качественные показатели, что позволит осуществлять мониторинг существующего состояния социального партнерства в условиях конкретного предприятия и государственный контроль за принятием управленческих решений в условиях достаточно подвижной системы социально-трудовых отношений. В перспективе дальнейшие исследования в данном направлении должны быть ориентированы на развитие теоретических основ и наработки действенных механизмов регулирования социально-трудовых отношений.